Road accident by reckless driving and speeding...review on road traffic law / Wahiidah Bakhtiar, Nor Balqis Ardiansa and Zamzilah Fairuz Kamarul Zaman - Bakhtiar, Wahiidah; Ardiansa, Nor Balqis; Zamzilah Fairuz, Kamarul Zaman (2008)
Road traffic injuries are a hidden global epidemic. Though millions are killed and injured every year, few are aware of the heavy human and economic toll of crashes, particularly in developing nations. Everyday, Malaysia faces the tragedy of 611 accidents, 16 deaths, 33 severely injured and 104 contended lightly injured. The percentage of Motor and deaths is highest in China (64%) and Malaysia is the second highest with 57%. Although there had been so many amendments prior to deter the situation, the rates still increasing. Thus, we attempt to take it a step higher by trying to criminalize these offences and to come with other solution that might be work this situation.